2023
DOI: 10.3390/vetsci10060392
|View full text |Cite
|
Sign up to set email alerts
|

Normal Range for the Schirmer Tear Test and Intraocular Pressure in Healthy Latvian Darkhead Lambs and Ewes

Liga Kovalcuka,
Nelli Alexandra Margarethe König,
Pia Valentina Helen Petersen
et al.

Abstract: A complete ophthalmological examination, including basic diagnostic tests such as the Schirmer tear test (STT) and intraocular pressure (IOP) measurement performed by tonometry in particular species and breeds, is essential for obtaining a clear diagnostic result and avoiding diagnostic misinterpretations. STT and IOP values have been poorly described for sheep. Therefore, this study aimed to determine the normal range for STT and tonometry values in clinically normal Latvian Darkhead lambs and ewes. Both eyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Similar to that observed in dogs, significantly higher IOP was noted in sheep with a mean difference of 4.48. To the best of our knowledge, no previous study by Kovalcuka et al [19] reported the difference between sheep tonometer measurements.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similar to that observed in dogs, significantly higher IOP was noted in sheep with a mean difference of 4.48. To the best of our knowledge, no previous study by Kovalcuka et al [19] reported the difference between sheep tonometer measurements.…”
Section: Discussionmentioning
confidence: 91%
“…To the best of our knowledge, no previous study by Kovalcuka et al . [ 19 ] reported the difference between sheep tonometer measurements.…”
Section: Discussionmentioning
confidence: 99%